On the Neutrality of Socially Responsible Investing - Lutz Arnold (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper analyzes socially responsible investment in the Walrasian model with uncertainty. It proves the following neutrality result: if each consumer's utility function with social responsibility is a function of her utility without social responsibility and asset holdings and if financial assets guarantee market completeness independently of stock payoffs, then socially responsible investment changes nothing but investors' financial portfolios and their subjective utilities, leaving resource allocation, goods prices, and asset prices completely unaffected. That is, with complete financial markets SRI is neutral unless it also has an impact on agents'consumption choices. The one-good representative agent version of the model is used to show that with incomplete markets, by contrast, neutrality of socially responsible is the exception rather than the rule.
Keywords: D51; 330; socially responsible investing; Modigliani-Miller theorem; general equilibrium